Performance Assessment Based On Reliability In Huron Machines Using Cost Of Unreliability (cour) Method Using Cost Of Poor Maintenance (copm) Analysis In Pt. Pindad (PERSERO) - Ida Bagus Yoga Samkhyaita; Fransiskus Tatas Dwi Atmaji; Judi Alhilman (eProceedings of Engineering, 2019)
Abstrak PT PINDAD (PERSERO) merupakan perusahan yang bergerak di bidang alat utama sistem persenjataan dan produk komersial di Indonesia. PT PINDAD (PERSERO) memproduksi senjata dan munisi, kendaraan khusus, bahan peledak, produk komponen, sarana, dan prasarana dalam bidang trasnportasi, dan produk alat berat. Dengan adanya proses produksi maka diperlukan perbaikan setelah mesin mengalami breakdown. Perbaikan atau perawatan sangat penting dalam meminimasi terjadinya ganguan pada produksi. Mesin Huron merupakan salah satu mesin di PT PINDAD (PERSERO). Permasalahan yang diteliti yaitu, penyebab terjadinya kerusakan pada mesin Huron, menentukan nilai COUR pada mesin Huron, dan pengaruh menggunakan analisis COPM yang digunakan untuk mengidentifikasi kelemahan pada kinerja perawatan di PT.PINDAD (PERSERO). Dari hasil pengolahan data yang telah dilakukan dengan metode COUR didapatkan biaya yang disebabkan oleh ketidakandalan sistem yang berdasarkan corrective time sebesar Rp 130.119.673 dan berdasarkan downtime sebesar Rp 1.370.731.116. Sedangkan untuk analisis COPM diperoleh bahwa terdapat tiga jenis kegiatan yang perlu dioptimalkan dan tiga jenis kegiatan yang perlu dikurangi. Kegiatan yang perlu melakukan pengoptimalan adalah kegiatan pemeliharaan bahan lain untuk pemeliharaan, lubricants, logistik. Sedangkan kegiatan yang perlu dikurangi adalah kegiatan lost production time, jam kerja untuk pemeliharaan, dan pemeliharaan exchange parts. Kata kunci: Cost of Unreliability, Cost of Poor Maintenance, Preventive Maintenance, Corrective Maintenance Abstrack PT PINDAD (PERSERO) is an Indonesian company that engages in the primary production of weapon systems and commercial products. PT PINDAD (PERSERO) produces weapons, ammunitions, exclusive vehicles, explosives, component products, various tools and infrastructure in relation to transport, as well as heavy equipment and machineries. With these processes of production, regular upkeeping is needed when machinery breakdowns occur. Maintenance and repairment is an important aspect as it minimizes production failures and errors. The Huron machine is one of the equipment used in the upkeeping process by PT PINDAD (PERSERO). The observations of this report are to identify the culprit of breakdowns of the Huron machine, to determine the COUR value of the Huron machine and the effects of using the COPM analysis that is required to identify weaknesses in the upkeeping performance at PT.PINDAD (PERSERO). From the processed data achieved with the COUR methoda cost estimation is attained by poor system due to corrective time at Rp 130.119.673 and due to downtime at Rp 1.370.731.116.. Meanwhile, for the COPM analysis, three types of activities were found to be in need of optimization and three types of activities were found to be in need of reduction. Therefore, the activities required for optimization are maintenance activities of other materials for maintenance, lubrication and logistics. On the other hand, the activities that are needed to be reduced are times for lost productions, times for maintenance activities and the maintenance of exchange parts. Keywords: Cost of Unreliability, Cost of Poor Maintenance, Preventive Maintenance, Corrective Maintenanc